2007
DOI: 10.1007/s10865-007-9135-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in self-efficacy and dietary adherence: the impact on weight loss in the PREFER study

Abstract: Findings from studies examining self-efficacy and its relationship to weight loss have been inconsistent. We examined self-efficacy specific to changing eating behaviors in the PREFER trial, an 18-month behavioral weight-loss study, to determine if self-efficacy and dietary adherence were associated with weight change, and what impact self-efficacy had on weight change after controlling for adherence. Measurements included the weight efficacy lifestyle (WEL) questionnaire, body weight, self-reported fat gram i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
4
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(133 citation statements)
references
References 53 publications
7
117
4
5
Order By: Relevance
“…Responses to five subscales of Negative Emotions, Social Pressure, Availability, Physical Discomfort, and Positive Activities (e.g., "I can resist eating when I am watching TV") range from 0 (Not confident) to 9 (Very confident), and are summed. Internal consistencies ranged from .70 to .90 (Clark et al, 1991), and the predictive validity was acceptable in multiple studies (Warziski, Sereika, Styn, Music, & Burke, 2008).…”
Section: Methodsmentioning
confidence: 92%
“…Responses to five subscales of Negative Emotions, Social Pressure, Availability, Physical Discomfort, and Positive Activities (e.g., "I can resist eating when I am watching TV") range from 0 (Not confident) to 9 (Very confident), and are summed. Internal consistencies ranged from .70 to .90 (Clark et al, 1991), and the predictive validity was acceptable in multiple studies (Warziski, Sereika, Styn, Music, & Burke, 2008).…”
Section: Methodsmentioning
confidence: 92%
“…Past research has found that improvement in self-efficacy over time is associated with greater weight loss ( Warziski et al, 2008;Wingo et al, 2013). However, among nonwhite samples, the role of selfefficacy in weight loss is mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity researchers have learned that improvement in self-efficacy is associated with weight loss ( Clark, Abrams, Niaura, Eaton, & Rossi, 1991;Warziski, Sereika, Styn, Music, & Burke, 2008). Conversely, lower rates of self-efficacy have been linked with a decreased likelihood of practicing weight management behaviors ( Palmeira et al, 2007;Shin et al, 2011).…”
mentioning
confidence: 99%
“…Dessa forma, desenvolver estratégias que visem o aumento da AE dos indivíduos se configura como uma das possibilidades para trabalhar a mudança de estilo de vida e, consequente, melhora no quadro das doenças assim como da SM. Sugere-se uma avaliação pós-tratamento com o objetivo de verificar se haverá aumento no nível de AE como observado em outros estudos (Bernier & Avard, 1986;Jeffery et al, 1984;Warziski, Sereika, Styn, Music, & Burke, 2008).…”
Section: Discussão E Considerações Finaisunclassified